Population Exposure to Phthalate‐containing Drugs. Issue 3 (18th May 2017) - Broe, Anne; Ennis, Zandra Nymand; Pottegård, Anton; Hallas, Jesper; Ahern, Thomas; Damkier, Per
Abstract: Phthalates are known endocrine disruptors. Not commonly recognized, phthalates are used as excipients in a number of drug formulations. We aimed to describe the sale of phthalate‐containing drugs in Denmark from 2004 to 2015. National data on annual sale of medications (tablets only) were accessed from medstat.dk. Data from the Danish Medicines Agency on phthalate content per tablet were merged with data on total sale for each active substance and drug formulation. We used the 'defined daily dose' (DDD) as the unit of sale and calculated the total amount of phthalate (mg) dispensed per 1000 inhabitants. Specific tablet content was compared with the maximum daily exposure limits defined by regulatory agencies for diethyl phthalate (DEP) and dibutyl phthalate (DBP) of 4.0 and 0.01 mg/kg/day, respectively. Use of phthalate‐containing drugs in Denmark was common. We found 154 drug products containing five different phthalates. Two low‐molecular‐weight phthalates and three high‐molecular‐weight phthalates were identified, with a total sale of 59.4 and 112 DDD per 1000 inhabitants per day during the study period, respectively. The highest amount of DBP was found in multi‐enzymes (24.6–32.8 mg per DDD) and mesalazine (12.5–26.4 mg per DDD). Budesonide, lithium and bisacodyl also exceeded the DBP exposure limit of 0.01 mg/kg/day. Other drugs had high levels of DEP, although not exceeding the exposure limit. Sales of phthalate‐containing drugs in Denmark from 2004 to 2015 were substantial, and phthalate exposure from several products exceeded the regulatory exposure limit introduced in 2014.